DEVELOPMENT OF ETHNOPANGAN-BASED DIGITAL POCKET BOOKS LOCAL WISDOM TO INCREASE LEARNING MOTIVATION AND AN ATTITUDE OF CARING FOR THE ENVIRONMENT IN MATERIAL BIODIVERSITY - Alya Nur Abdila; Khairiza Lubis; Hasruddin (SOSIOEDUKASI, 2026)
Biodiversity learning requires contextual learning resources that can connect scientific concepts with students' local environments and cultural experiences. However, conventional learning materials often provide limited opportunities for students to explore local biological resources and develop environmental responsibility. This study aimed to develop an ethnofood-based digital pocket book integrating the local wisdom of Langkat Regency for biodiversity learning and to evaluate its feasibility and effectiveness in improving students' learning motivation and environmental care attitudes. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants involved material experts, media experts, language experts, a biology teacher, and tenth-grade students of SMA Negeri 1 Stabat. Data were collected through validation sheets, teacher and student response questionnaires, learning motivation questionnaires, environmental care attitude questionnaires, observations, and analyzed using descriptive statistics and N-Gain analysis. The results showed that the digital pocket book achieved high feasibility based on expert validation scores for material (90.00%), media (94.16%), language (94.44%), and teacher response (94.29%). The implementation of the media improved students' learning motivation with an N-Gain score of 73.30% and environmental care attitudes with an N-Gain score of 75.03%. These findings indicate that the ethnofood-based digital pocket book is a valid, practical, and effective learning resource that integrates local wisdom, digital technology, and sustainability-oriented biodiversity education.